America as empire global leader or rogue power? - Garrison, Jim (Berret-Koehler Publishers, 2004)
"But the core question, Garrison asserts, is what kind of empire can and should America be? As the sole superpower, America must lead in shaping a new global order, just as after World War II Roosevelt and Truman took the lead in shaping a new international order. That international order is now crumbling under the pressures of globalization, persistent poverty, terrorism, fundamentalism, and U.S. foreign policy itself."--BOOK JACKET